2019
DOI: 10.1002/mgg3.979
|View full text |Cite
|
Sign up to set email alerts
|

Genetic biomarkers related to hemarthrosis, inflammation, and cartilage structure in pediatric patients with hemophilic arthropathy

Abstract: BackgroundThe pathophysiology of hemophilic arthropathy is complex and not completely understood. In this study, we aimed to identify biomarkers that can affect the hemophilic arthropathy severity.MethodsFifty patients were analyzed for biomarker frequencies; in 37 patients, articular symptoms were evaluated based on the physical joint examination score, and in 18, it was based on magnetic resonance imaging. Eight polymorphisms, namely FV 1691G>A, FII 20210G>A, MTHFR 677C>T and 1298A>C, TNFα‐308G>A and ‐238G>A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“… 29 A small study reported that patients with the MTHFR variants MTHFR 677TT or MTHFR 1298AC had a higher number of affected joints or a higher degree of effusion, respectively, compared to patients with other genotypes. 30 Furthermore, this study also found a positive association between genetic biomarkers related to inflammation and number of subchondral cysts.…”
Section: Variables Influencing Joint Outcomessupporting
confidence: 62%
See 2 more Smart Citations
“… 29 A small study reported that patients with the MTHFR variants MTHFR 677TT or MTHFR 1298AC had a higher number of affected joints or a higher degree of effusion, respectively, compared to patients with other genotypes. 30 Furthermore, this study also found a positive association between genetic biomarkers related to inflammation and number of subchondral cysts.…”
Section: Variables Influencing Joint Outcomessupporting
confidence: 62%
“… 30 Furthermore, this study also found a positive association between genetic biomarkers related to inflammation and number of subchondral cysts.…”
Section: Variables Influencing Joint Outcomessupporting
confidence: 62%
See 1 more Smart Citation
“…Lopez‐Jimenez et al . have reported that carriers of the TNFα‐308G>A variant have a larger number of subchondral cysts, 17 platelet aggregation, 18 and the innate immune response pathways that play a fundamental role in pathogen recognition and the activation of innate immunity such as nucleotide‐binding oligomerization domain‐containing protein 2, and toll‐like receptor 10 . 19 …”
Section: Factors Contributing To Arthropathymentioning
confidence: 99%
“…However, as patients with the same mutation often have different bleeding phenotypes, other genetic factors such as inherited thrombophilia may also be involved. 16 Genetic susceptibility to more rapid joint damage progression also involves gene polymorphisms associated with an increased expression of pro-inflammatory cytokines such as tumor necrosis factor (TNF)α. Lopez-Jimenez et al have reported that carriers of the TNFα-308G>A variant have a larger number of subchondral cysts, 17 platelet aggregation, 18 and the innate immune response pathways that play a fundamental role in pathogen recognition and the activation of innate immunity such as nucleotide-binding oligomerization domain-containing protein 2, and toll-like receptor 10 . 19…”
Section: Genetic Susceptibilitymentioning
confidence: 99%